2003
DOI: 10.1016/s1010-7940(02)00814-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes following VATS lobectomy for non-small cell bronchogenic carcinoma

Abstract: VATS lobectomy is a safe procedure which is associated with a low probability for conversion to open thoracotomy. The patterns of cancer recurrence do not suggest inadequate local clearance while the long-term survival data for Stage I NSLC cases is encouraging. We believe that this technique should become the operation of choice for early stage NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(137 citation statements)
references
References 20 publications
7
124
0
6
Order By: Relevance
“…In addition, the extended survival may be further exaggerated by the limited number of patients available (44,45). We consi dered that patient bias may be a critical bias, and it should have influence on survival.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the extended survival may be further exaggerated by the limited number of patients available (44,45). We consi dered that patient bias may be a critical bias, and it should have influence on survival.…”
Section: Discussionmentioning
confidence: 94%
“…Blazeby et al (11) evaluated the quality of life of esophageal cancer patients who received surgery or palliative treatment using EORTC QLQ-C30 and observed that the quality of life of the former was significantly higher compared to that of the latter, suggesting that surgical treatment may be a preferred choice for patients with esophageal cancer. Studies on the effect of VATS on the quality of life are currently more focused on patients with lung cancer (12,13). To the best of our knowledge, this is the first study on the effect of VATS on the quality of life of patients with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A VATS approach does not compromise survival for lung cancer patients. 5-year survival for VATS lobectomy show outcomes that are typically expected for surgical treatment of lung cancer (McKenna et al, 2006;Walker et al, 2003;Yamamoto et al, 2010;Rueth & Andrade, 2010). With no proven difference in stage specific survival VATS lobectomy can be recommended for clinical stage I and II non-small cell lung cancer.…”
Section: Survivalmentioning
confidence: 99%
“…Table 1 shows typical complications after VATS lobectomy. Mortality rates for VATS lobectomy vary from 0% to 2,6% (McKenna et al, 2006;Roviario et al, 2003;Walker et al, 2003).…”
Section: Complicationsmentioning
confidence: 99%